Chitosan oligosaccharide activates brown adipose tissue by modulating the gut microbiota and bile acid pathways based on faecal microbiota transplantation - Weijun Lun; Jingwen Zhou; Yan Bai; Qishi Che; Hua Cao; Jiao Guo; Zhengquan Su (Journal of Functional Foods, 2023)
Objective: To study the effect of chitosan oligosaccharide with a molecular weight ≤3000 Da (COSM) on the energy metabolism of obese mice after faecal bacteria transplantation. Methods: A pseudo-germ-free obese mouse model was established. 16S rRNA was used to analyse the microflora of the caecal contents of mice in each group to judge whether the model was successful or not. The faecal flora of donor mice was transplanted into a pseudo-germ-free obese mouse model by tube feeding, and the lipid-lowering effect of COSM intervention on the intestinal flora was detected. The correlations among the bile acid composition, key intestinal microbial markers, and serum bile acid spectrum were analysed. At the same time, the influence of intestinal microorganisms on the TGR5-Dio2-UCP1 signalling pathway after faecal bacteria transplantation was explored. Conclusion: COSM can regulate the intestinal microecology and serum bile acid pool of pseudo-germ-free obese mice through intestinal microorganisms, thus activating the energy metabolism pathway to play a role in weight loss.